2007
DOI: 10.1017/s0030605307001044
|View full text |Cite
|
Sign up to set email alerts
|

Are poverty and protected area establishment linked at a national scale?

Abstract: The debate about poverty and conservation draws mainly on local case studies, particularly of the impacts of protected areas. Although it is clear that local and contingent variables have important effects on the social and economic impacts of protected area establishment, it is not known whether there is a general relationship between national wealth and the area, number and type of protected area designated. Here we conduct such an analysis. Our results suggest that wealthy countries have a larger number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
2

Year Published

2009
2009
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 22 publications
3
34
0
2
Order By: Relevance
“…The campaign to increase the proportion of protected areas significantly was first seriously promoted at the 1982 World Parks Congress in Bali, where all nations were set a target of having 10% of countries under protection (Naughton-Treves, 2005). At the World Parks Congress in 2003, it was reported that the number of protected areas had tripled over the preceding 20 years bringing the total to an estimated 100 000 worldwide (World Parks Congress, 2003), although some put the current figure at more than 105 000 (Upton et al, 2008). The impact of these expanding protected areas on the livelihoods of neighbouring communities, has however largely been ignored by conservation authorities.…”
Section: People Or/and Protected Areas: From Strict Reservation To Camentioning
confidence: 99%
See 3 more Smart Citations
“…The campaign to increase the proportion of protected areas significantly was first seriously promoted at the 1982 World Parks Congress in Bali, where all nations were set a target of having 10% of countries under protection (Naughton-Treves, 2005). At the World Parks Congress in 2003, it was reported that the number of protected areas had tripled over the preceding 20 years bringing the total to an estimated 100 000 worldwide (World Parks Congress, 2003), although some put the current figure at more than 105 000 (Upton et al, 2008). The impact of these expanding protected areas on the livelihoods of neighbouring communities, has however largely been ignored by conservation authorities.…”
Section: People Or/and Protected Areas: From Strict Reservation To Camentioning
confidence: 99%
“…Ever since the Stockholm Conference on the Human Environment in 1972, the links between environment and development and, more specifically, conservation and poverty, have been intensely discussed and fiercely debated -a debate that has gained momentum in recent times (Andam et al, 2010;De Sherbinin, 2008;Dudley et al, 2008;Simpson, 2008;Upton et al, 2008;Wells & McShane, 2004). Scrutinising the social role of protected areas and their impact on rural livelihoods and development has become an increasingly central component of this debate (Naughton-Treves et al, 2005;Simpson, 2009;Spenceley, 2008b).…”
Section: Protected Areas As Platforms For Poverty Mitigationmentioning
confidence: 99%
See 2 more Smart Citations
“…Some see conservation as the main goal and poverty alleviation as an afterthought (Sanderson and Redford 2004), whereas others argue that separating parks from people is a false dichotomy (West and Brockington 2006). Because many of the most threatened areas in tropical regions are inhabited by poor people dependent on natural resources, conservation policy must take them into account (Cordeiro et al 2007, de Sherbinin 2008, Upton et al 2008. Although the use of terms such as "integrated conservation and development" may have fallen out of favor, many interventions do, and will continue to, consider the well-being of populations inhabiting and surrounding protected areas ).…”
Section: Introductionmentioning
confidence: 99%